A Utilitarian Justification of Desert in Distributive Justice - Kristjánsson, Kristján (Journal of moral philosophy, 2005)
Abstract We cannot conclude from the assumptions that justice is a virtue and desert is an ingredient in justice that desert claims themselves express a virtue. It could be that desert is morally neutral, or even immoral, and that there are other aspects of justice which make it all-in-all virtuous. We need, in other words, an independent moral justification of desert and desert-based emotions. In this paper I take on the challenge of articulating and defending a utilitarian justification of desert in distributive justice. I argue, first, that while there may be ways of accommodating desert-concerns in liberal theory, this cannot, in the view of liberals themselves, be done without considerable cost to the ideals that are closest to their hearts. By contrast, I suggest that a deceptively simple utilitarian (Millian) defence of desert can be made to work. Finally, I attempt to surmount various possible objections that might be raised against my utilitarian justification and conclude that none of them confutes it.